Numerical investigation on natural convective heat transfer of Al2O3-water nanofluids (About the effect of thermophysical properties) - Masato AKAMATSU; Takuto KAMEYAMA; Yuki YOMOGITA; Mitsuo IWAMOTO; Hiroyuki OZOE (Nihon Kikai Gakkai ronbunshu, 2016)
Nanofluids are suspension dispersed nano-scale particles in a base fluid. In this study, natural convective heat transfer characteristics of Al2O3-water nanofluids in a vertical cylindrical container heated from below and cooled from above are investigated by transient three-dimensional numerical computations. Thermophysical properties of Al2O3-water nanofluids are estimated by either the conventional prediction equations or the experimental correlation equations reported by Khanafer and Vafai. The validation of the analysis program developed in the present study is carried out by comparing the computed average Nusselt numbers of the Rayleigh-Benard convection of water for Ra = 2500, 5000, 7500, and 10000 with Silveston's experimental data. A grid independency study is also carried out by computing the natural convection of water for Ra = 105. When thermophysical properties estimated by the conventional prediction equations are applied, the heat transfer rates of Al2O3-water nanofluid natural convection increase with the increase of the volume fraction of the nanoparticles for Ra = 104, and 105 compared with those of water. When thermophysical properties estimated by the experimental correlation equations are applied, the heat transfer rates of Al2O3-water nanofluid natural convection decrease with the increase of the volume fraction of the nanoparticles. The decrease of the convective heat transfer rates agrees with the experimental results reported by Li and Peterson qualitatively. Thermophysical property equations for estimating both at least effective viscosity and effective thermal conductivity are necessary to compute natural convective heat transfer characteristics of Al2O3-water nanofluids more accurately.